1983
DOI: 10.1039/c39830000423
|View full text |Cite
|
Sign up to set email alerts
|

Generation of ethyl thioxoacetate, a dienophilic thioaldehyde

Abstract: Ethoxycarbonylmethanesulphenyl chloride reacts with triethylamine t o give the transient thioaldehyde, ethyl thioxoacetate, which has been trapped, in situ, by cycloaddition to various conjugated dienes.Until recently,lT2 cycloaddition reactions of thioaldehydes with conjugated dienes had not been reported, although the syn-thetic utility of the Diels-Alder adducts of other thiocarbonyl compounds is well a p p r e ~i a t e d . ~The neglect of simple4 thio-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Tetrachlorothiophene 1,l-dioxide (4) is known to be a versatile Diels-Alder diene and reacts particularly with electron-rich alkenes by cycloaddition with concomitant extrusion of sulphur dioxide.' Thus with cyclohexene, the hexahydronaphthalene ( 5 ) is produced (Scheme 2). We have found that the analogous S,N-ylides (6) (easily prepared from tetrachlorothiophene and the appropriate azides) undergo similar cycloadditions at almost comparable rates to give the same adducts (8) in good yield (Scheme 3).…”
mentioning
confidence: 99%
“…Tetrachlorothiophene 1,l-dioxide (4) is known to be a versatile Diels-Alder diene and reacts particularly with electron-rich alkenes by cycloaddition with concomitant extrusion of sulphur dioxide.' Thus with cyclohexene, the hexahydronaphthalene ( 5 ) is produced (Scheme 2). We have found that the analogous S,N-ylides (6) (easily prepared from tetrachlorothiophene and the appropriate azides) undergo similar cycloadditions at almost comparable rates to give the same adducts (8) in good yield (Scheme 3).…”
mentioning
confidence: 99%
“…The HDA reactions of ethyl thioxoacetate 983 with various dienes were investigated by Bladon et al 490 producing thiopyran derivatives. Reactions were carried out by in situ generation of ethyl thioxoacetate 983 by treatment of ethyl mercaptoacetate with NCS in dry benzene at room temperature for 2 h, followed by addition of a solution of a diene in benzene and methanol containing Et 3 N at room temperature.…”
Section: Thiopyransmentioning
confidence: 99%
“…Kirby and coworkers [3][4][5][6][7][8] reported the formation of ethyl thioxoacetate (3) from sulphonyl chloride (2) by elimination of hydrogen chloride with triethylamine. e thioaldehyde was trapped by a variety of 1,3-dienes such as 2,3-dimethylbutadiene (4), cyclohexadiene (5), anthracene (6a), 9,10-anthracene (6b), and thebaine (7).…”
Section: Introductionmentioning
confidence: 99%